2003
DOI: 10.1038/ng1262
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of D4Z4 in 4q-linked and non-4q-linked facioscapulohumeral muscular dystrophy

Abstract: The autosomal dominant myopathy facioscapulohumeral muscular dystrophy (FSHD1, OMIM 158900) is caused by contraction of the D4Z4 repeat array on 4qter. We show that this contraction causes marked hypomethylation of the contracted D4Z4 allele in individuals with FSHD1. Individuals with phenotypic FSHD1, who are clinically identical to FSHD1 but have an unaltered D4Z4, also have hypomethylation of D4Z4. These results strongly suggest that hypomethylation of D4Z4 is a key event in the cascade of epigenetic events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
357
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(374 citation statements)
references
References 13 publications
15
357
0
2
Order By: Relevance
“…The ALT phenotype of LB188 cell line, established from a rhabdomyosarcoma tumor (F Brasseur, unpublished data), was further confirmed by the absence of telomerase activity assessed by the telomeric repeat amplification protocol (Supplementary Figure 1). For the evaluation of subtelomeric DNA methylation levels, we chose to analyse the methylation status of the non-satellite D4Z4 subtelomeric repeats located at 4q35.2 and 10q26.3, as (1) the nucleotide sequence of the corresponding 3.3-kb D4Z4 repeats has been determined (Cacurri et al, 1998), (2) this region is known to be subjected to methylation on cytosine residues in normal tissues (van Overveld et al, 2003) and (3) the last D4Z4 repeat is mapped 23-24 kb from the 4q or 10q telomere in the current reference genome build (36.3) and further analyses indicated that D4Z4 is the last repetitive element in 4q and 10q (Riethman, 2008). Primers were designed to specifically amplify a 380-bp region of the D4Z4 repeat unit derived from 4q35.2 and 10q26.3 and containing 31 CpG dinucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…The ALT phenotype of LB188 cell line, established from a rhabdomyosarcoma tumor (F Brasseur, unpublished data), was further confirmed by the absence of telomerase activity assessed by the telomeric repeat amplification protocol (Supplementary Figure 1). For the evaluation of subtelomeric DNA methylation levels, we chose to analyse the methylation status of the non-satellite D4Z4 subtelomeric repeats located at 4q35.2 and 10q26.3, as (1) the nucleotide sequence of the corresponding 3.3-kb D4Z4 repeats has been determined (Cacurri et al, 1998), (2) this region is known to be subjected to methylation on cytosine residues in normal tissues (van Overveld et al, 2003) and (3) the last D4Z4 repeat is mapped 23-24 kb from the 4q or 10q telomere in the current reference genome build (36.3) and further analyses indicated that D4Z4 is the last repetitive element in 4q and 10q (Riethman, 2008). Primers were designed to specifically amplify a 380-bp region of the D4Z4 repeat unit derived from 4q35.2 and 10q26.3 and containing 31 CpG dinucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…Epimutation of MLH1 resembles aberrations of parental imprinting 25 and the silencing of expanded triplet repeats 26 , but MLH1 is not an imprinted gene, and the clearing of the epimutation in individual TT's daughter militates against an underlying defect in the affected locus as a cause of silencing. More similar is the occurrence of facioscapulohumeral muscular dystrophy in individuals and kindreds who have hypomethylation of the D4Z4 repeat array 27 . The occurrence of germline epimutation at MLH1 suggests that normally active loci can become silent chromatin in the germ line, perhaps through association with constitutively silent sequences.…”
mentioning
confidence: 87%
“…However, both their D4Z4 alleles show hypomethylation. These findings suggest a central role of D4Z4 hypomethylation in the pathogenesis of FSHD [1] . Chromatin of eukaryotic organisms can roughly be divided into relatively hypomethylated euchromatin and highly methylated heterochromatin.…”
Section: Introductionmentioning
confidence: 67%
“…In healthy individuals, the chromatin structure of the D4Z4 region on chromosome 4q35 is highly methylated, and resembles that of heterochromatin or transcriptional inactive euchromatin [4][5][6] . A currently favored hypothesis is that the marked hypomethylation of the D4Z4 region in FSHD might cause a change in the chromatin structure, and consequently a transcriptional deregulation of one or more genes in the vicinity, or at a distance of the D4Z4 repeat array [1,6] . As DNA methylation and demethylation are reversible processes, DNA methylation levels and patterns can potentially be influenced [2] .…”
Section: Introductionmentioning
confidence: 99%